The Female Body as a Sacred Symbol: An Analysis of Goddess Theology and its Relation to Feminist Archaeology and Feminist Art History - Siler, Miranda L. (Tufts Archival Research Center, 2017)
This thesis explores the connections between contemporary Neopagan Goddess Worship and Paleolithic and Neolithic female figurines.